Transient seepage and slope stability analysis for rainfall induced landslide: a case study - Gofar, Nurly; Lee, Min Lee; Asof, Marwan (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)
A transient seepage and slope stability analyses were carried out for a case of rainfall-induced landslide in Air Laya Indonesia . The landslide occurred in December 2002 on a dumping area of an open coal mining site. This study examined the mechanism causing the slope failure based on transient analysis between April 21, 2001 and December 1, 2002. The slope profile was simulated using a seepage analyzing tool, VADOSE/W and the soil properties were determined based on field and laboratory data. The saturation profile resulted from seepage analysis was exported to SLOPE/W for the slope stability evaluation. The results show that the main factor contributing to the landslide is the reduction of shear strength due to increase in soil moisture content impelled by the formation of tension cracks on the ground surface of the slope.